Pengaruh Karakteristik Dewan Direksi Terhadap Kualitas Laporan Keberlanjutan: Indeks SRI KEHATI - Hartawan, I Made Widi (LPPM POLITEKNIK LP3I BANDUNG, 2025)
This research aims to investigate the influence of the attributes of the board of directors in Indonesia and the quality of the sustainability reports. The novelty of this research is to integrate the characteristics of the board of directors in a research model that focuses on the quality of the report. Measurement of the characteristics of the board of directors uses variables of educational background, work experience, and gender diversity. The upper-echelon theory perspective is used in analyzing the relationship between the characteristics of the board of directors and the quality of sustainability reports for firms listed on the SRI KEHATI index during the period from 2021 to 2023. This investigation employs a multiple regression analysis model and utilizes STATA 12 software for data processing. The results showed that educational background doesn’t have a significant negative effect on the quality of sustainability reports. Work experience and gender diversity don’t have a significant positive effect on the quality of sustainability reports.